Corrosion fatigue crack growth behavior of pipeline steel under underload-type variable amplitude loading schemes. (1st September 2015) - Yu, Mengshan; Xing, Xiao; Zhang, Hao; Zhao, Jiaxi; Eadie, Reg; Chen, Weixing; Been, Jenny; Boven, Greg Van; Kania, Richard
Abstract: This investigation attempts to rationalize various near-neutral pH corrosion fatigue (CF) failure scenarios found during pipeline operations, which continues to be a major consideration in pipeline integrity. The phenomenon is often referred to as stress corrosion cracking (SCC) but as will be discussed is more properly considered as CF. Existing CF (SCC) models predict a service life of more than 100 years for gas pipelines, as compared with the 20–30 years typically seen in the field when these mechanisms are operative. It has been identified from analyzing pressure fluctuations recorded in the field that the underload-type variable amplitude loading schemes often found within 30 km downstream of a compressor station are the most prone to crack growth, and these locations comprise more than 70% of all-service and hydrostatic-test failures attributed to stress cracking. In this investigation, underload-type variable amplitude loading schemes were designed and used for crack growth measurements in pipeline steel in near-neutral pH environments. Crack growth enhancement by a factor of 10 was found under the underload-type variable amplitude cyclic loading, as compared with the constant amplitude cyclic loading. There also exist two distinct regimes of crack growth behavior over the range of loading frequency from 5.0 × 10 −1  Hz to 10 −5  Hz under such variable amplitude fatigue. Crack growth rate was found to increase with decreasing loading frequency down to 10 −3  Hz, while it remained constant below 10 −3  Hz. This critical loading frequency was successfully modeled based on the crack growth mechanisms identified. The outcome of the investigation agrees well with the failures experienced in the field.